Human Development Report 2007/2008 : fighting climate change : human solidarity in a divided world - United Nations Development Programme (New York : United Nations Development Programme ; Palgrave Macmillan, 2007)
The report ...calls for a "twin track approach that combines stringent mitigation to limit 21st Century warming to less than 2°C (3.6° F) with strengthened international cooperation on adaptation. On mitigation, the authors call on developed countries to ... cut greenhouse gas emissions by at least 80% of 1990 levels by 2050. It advocates a mix of carbon taxation, more stringent cap-and-trade programmes, energy regulation, and international cooperation on financing for low-carbon technology transfer. Turning to adaptation, the report warns that inequalities in ability to cope with climate change are emerging as an increasingly powerful driver of wider inequalities between and within counties. It calls on rich countries to put climate change adaptation at the centre of international partnerships on poverty reduction.
Fighting climate change: human solidarity in a divided world -- The 21st Century climate challenge -- Climate shocks: risk and vulnerability in an unequal world -- Avoiding dangerous climate change: strategies for mitigation -- Adapting to the inevitable: national action and international cooperation --
Includes bibliographical references and indexes.
Akbar Ali Khan Collection
Keywords: United Nations Development Programme; Climatic changes -- Environmental aspects; Climatic changes -- Economic aspects; Global warming; Global warming -- Economic aspects; Greenhouse gas mitigation